Evolving European guidance on the medical management of neovascular age related macular degeneration. Issue 9 (23rd August 2006) - Chakravarthy, U; Soubrane, G; Bandello, F; Chong, V; Creuzot-Garcher, C; Dimitrakos, S A; Korobelnik, J-F; Larsen, M; Monés, J; Pauleikhoff, D; Pournaras, C J; Staurenghi, G; et al.
Abstract : Background: Until recently, only two options were available for the treatment of choroidal neovascularisation (CNV) associated with age related macular degeneration (AMD)—thermal laser photocoagulation and photodynamic therapy with verteporfin (PDT-V). However, new treatments for CNV are in development, and data from phase III clinical trials of some of these pharmacological interventions are now available. In light of these new data, expert guidance is required to enable retina specialists with expertise in the management of AMD to select and use the most appropriate therapies for the treatment of neovascular AMD. Methods: Consensus from a round table of European retina specialists was obtained based on best available scientific data. Data rated at evidence levels 1 and 2 were evaluated for laser photocoagulation, PDT-V, pegaptanib sodium, and ranibizumab. Other treatments discussed are anecortave acetate, triamcinolone acetonide, bevacizumab, rostaporfin (SnET2), squalamine, and transpupillary thermotherapy. Results: PDT-V is currently recommended for subfoveal lesions with predominantly classic CNV, or with occult with no classic CNV with evidence of recent disease progression and a lesion size ⩽4 Macular Photocoagulation Study (MPS) disc areas (DA). The new classes of anti-angiogenic agents—namely, pegaptanib sodium and ranibizumab (the latter when peer reviewed phase III data become available) are recommended for subfoveal lesions with any proportion of classic CNV or occult with no classic CNV. For juxtafoveal classic CNV, PDT-V or anti-angiogenic therapy should be considered if the new vessels are so close to the fovea that laser photocoagulation would almost certainly extend under the centre of the foveal avascular zone. For all other well demarcated juxtafoveal lesions and for extrafoveal classic lesions, laser photocoagulation remains the standard treatment. Therapy should be undertaken within 1 week of the fluorescein angiogram on which the clinical decision to treat is based. At each follow up, fluorescein angiography should be performed and best corrected visual acuity measured as a minimum requirement. Conclusions: These recommendations provide evidence based guidance for the choice and use of non-surgical therapies for the management of neovascular AMD. Revisions of the recommendations may be required as new data become available.